2014
DOI: 10.4329/wjr.v6.i7.471
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of mindfulness and meditation: Evidence from neuroimaging studies

Abstract: Mindfulness is the dispassionate, moment-by-moment awareness of sensations, emotions and thoughts. Mindfulness-based interventions are being increasingly used for stress, psychological well being, coping with chronic illness as well as adjunctive treatments for psychiatric disorders. However, the neural mechanisms associated with mindfulness have not been well characterized. Recent functional and structural neuroimaging studies are beginning to provide insights into neural processes associated with the practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(100 citation statements)
references
References 65 publications
4
92
0
4
Order By: Relevance
“…It is hypothesized that mindful emotion regulation is mediated by enhanced prefrontal cognitive control and concomitant downregulation of activity in limbic structures, including the amygdala. 72,78 It is possible that increased modulation of limbic structures via mindfulness-based approaches 36 could lead to further emotional overmodulation in individuals with PTSD+DS; however, it is also possible that mindfulness-based approaches may be associated with enhanced ability to accurately modulate limbic reactivity (e.g., via reducing or increasing top-down inhibition limbic regions, depending on the circumstances), as has been suggested by Tang and colleagues. 72 Thus, future work will be necessary to elucidate the relative effectiveness of mindfulness in improving both emotional under-and overmodulation in individuals with PTSD and with PTSD+DS.…”
Section: Prefrontal Modulation Of Limbic Structures and Mindfulnessmentioning
confidence: 92%
See 2 more Smart Citations
“…It is hypothesized that mindful emotion regulation is mediated by enhanced prefrontal cognitive control and concomitant downregulation of activity in limbic structures, including the amygdala. 72,78 It is possible that increased modulation of limbic structures via mindfulness-based approaches 36 could lead to further emotional overmodulation in individuals with PTSD+DS; however, it is also possible that mindfulness-based approaches may be associated with enhanced ability to accurately modulate limbic reactivity (e.g., via reducing or increasing top-down inhibition limbic regions, depending on the circumstances), as has been suggested by Tang and colleagues. 72 Thus, future work will be necessary to elucidate the relative effectiveness of mindfulness in improving both emotional under-and overmodulation in individuals with PTSD and with PTSD+DS.…”
Section: Prefrontal Modulation Of Limbic Structures and Mindfulnessmentioning
confidence: 92%
“…This is particularly pertinent, given that heightened resting state functional connectivity of the SN may indicate inappropriate use of the network in the absence of salient internal or external stimuli among individuals with PTSD. Conversely, several sources have indicated increased activity of the AI (a main node of the SN) during mindful states, 78,109,110 which may be construed as counterproductive given heightened resting-state activation of SN regions in patients with PTSD. Notably, in these studies it is not clear what aspect of mindfulness is used while the AI is active (e.g., attention to external stimuli v. awareness of mind wandering).…”
Section: J Psychiatry Neurosci 2018;43(1)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a review of several studies about mindfulness meditation in healthy participants showed that mindfulness impacts information processing in the medial cortex and associated DMN, insula and amygdala [94]. Also, structural imaging studies corroborate these findings, adding changes in the hippocampus as a result of mindfulness practice [94].…”
Section: Mindfulnessmentioning
confidence: 98%
“…However, a review of several studies about mindfulness meditation in healthy participants showed that mindfulness impacts information processing in the medial cortex and associated DMN, insula and amygdala [94]. Also, structural imaging studies corroborate these findings, adding changes in the hippocampus as a result of mindfulness practice [94]. Boccia, Piccardi, and Guariglia [95] highlight that meditation activates brain areas involved in processing self-relevant information, self-regulation, focused problem-solving, adaptive behaviour and interoception.…”
Section: Mindfulnessmentioning
confidence: 99%